EFFECTS OF Citrus hystryx AS FAT PROTECTOR ON UNSATURATED FATTY ACIDS, CHOLESTEROL AND CHEMICAL COMPOSITION OF LAMB MEAT - Tiven, N.C.; Siwa, I. P.; Joris, L. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
This study was conducted to determine the effect of Citrus hystrix as fat protector on unsaturated fatty acids, cholesterol and chemical composition of lamb meat. The research design applied was completely randomized design with 3 treatments and 5 replications. Fifteen local male lambs aged 9-12 months weighing 14-17 kg, were divided into 3 groups of different diet treatments (P0 : sheeps were only given a basal diet; P1 : sheeps are given basal diet and 3% cooking oil; P2 : sheeps are given basal diet, 3% cooking oil and protected by 3% Citrus hystrix powder). The data were analyzed by analysis of variance, the differences among treatments were tested by Duncan’s New Multiple Range Test. The results showed meat from sheeps that consume P2 diet has a total fatty acid and polyunsaturated fatty acids content were higher (P